The Chronology of Early Human Settlement in Three Gorges Region, China—Contribution of Coupled Electron Spin Resonance and Uranium-Series Dating Method - Han, Fei; Bahain, Jean-Jacques; Shao, Qingfeng; Sun, Xuefeng; Voinchet, Pierre; Xiao, Ping; Huang, Manchen; Li, Mengqi; Yin, Gongming (Frontiers in Earth Science, 2022)
The Three Gorges area, located in the geographic center of China, is a transition zone between mountain and plain areas, and a probable migration corridor for hominins and other mammals between South and North China. Detailed chronological information of the paleoanthropological evidence in this area could help us better understand the human evolution in East Asia. The OSL and U-series dating methods are two conventional dating methods generally adopted to date such sites, however their application were limited by the dating range – restricted to several hundred of millennia, and ambiguous stratigraphic relationship between the archaeological remains and the dating target materials. Cosmogenic nuclide burial dating of quartzite stone artifacts and coupled electron spin resonance and uranium-series dating (ESR/U-series) of fossil teeth have the potential to date Early-Middle Pleistocene hominin sites in Asia and were applied especially in China in recent years. However, the application of cosmogenic 26Al/10Be burial dating is limited in Three Gorges area because the geological context of most sites is dominated by limestone leading to the scarcity of quartz component in the fossil layer sediments. In this case, coupled ESR/U-series method plays a more important role in the establishment of the chronology of human settlement. In the Three Gorges area, by using coupled ESR/U-series method, we have dated several important Early and Middle Pleistocene hominin settlement sites, including Longgupo, Jianshi, Yunxian, Meipu, Bailongdong, Changyang and Yumidong sites. Based on our dating results, hominins were settled in Three Gorges area probably from the early stage of Early Pleistocene (~2.5-2.2 Ma) at Longgupo site to the late Middle Pleistocene to Late Pleistocene site of Yumidong site (~274-14 ka), and very likely to spread to other parts of East Asia during this time period. In view of the potential of coupled ESR/U-series dating on fossil teeth from the hominin sites in Three Gorges area, future work may consider the micro damage or non-destructive analysis of enamel fragment with ESR method and laser ablation ICP-MS techniques, that will make possible the direct dating of precious human fossils in China.